Ferroptosis of brain microvascular endothelial cells contributes to hypoxia‐induced blood–brain barrier injury. Issue 5 (12th April 2023) - Liu, Qiuling; Song, Tujing; Chen, Bing; Zhang, Jingjing; Li, Wen
Abstract: Hypoxia is pivotal to the pathogeneses of myriad disorders, especially hypoxic cerebropathy. Much is known about the damage to the blood–brain barrier (BBB) in response to hypoxia. Studies have shown that endothelial cell death is closely linked to functional impairment of BBB. Mounting evidences have demonstrated that ferroptosis, a new pathway regulating cell death, is implicated in brain injury. However, whether ferroptosis is involved in hypoxia‐induced BBB disruption remains ambiguous. Here, we utilized in vivo zebrafish and in vitro bEnd.3 cells to explore the correlation between endothelial ferroptosis and hypoxia‐induced BBB damage. We found that hypoxic treatment for 45 min can induce BBB disruption by triggering down‐regulation of claudin‐5 (CLDN5) both in zebrafish cerebrovascluar endothelial cells and bEnd.3 cells. Besides, in vitro and in vivo studies revealed the cysteine/glutamate antiporter xCT (also known as solute carrier family 7 member 11; SLC7A11) decrease, glutathione peroxidase 4 (GPX4) and glutathione (GSH) reduction, 4‐Hydroxynonenal (4‐HNE) increasement, malondialdehyde (MDA) upregulation and reactive oxygen species (ROS) accumulation in hypoxia group. Further mechanism studies indicated that hypoxia‐induced BBB damage might associate with microvascular endothelial cellular ferroptosis, since hypoxic exposure significantly activated the expression of ferroptosis‐related genes ( Ptgs2, Por, Lpcat3, Alox5, Alox12, Nfe2l2, and Ncoa4 ) and inhibited the expression of Slc7a11 . Additionally, the application of 20 μM ferrostatin‐1 (Fer‐1), a ferroptosis inhibitor, could partially alleviate BBB disruption under hypoxia, suggesting that inhibition of ferroptosis might be a potential strategy for some neurological diseases with BBB defect. Abstract : Endothelial ferroptosis in BBB disruption. Under normal condition, CLDN5, as a transmembrane protein, is involved in forming tight junctions to form BBBs and maintains central nervous system homeostasis. Under hypoxic condition, intracellular oxidative stress increases, manifested by an increase in Fe 2+ and oxidized radical/lipid peroxidation products in brain microvascular endothelial cells. Additionally, CLDN5 is down‐regulated and translocated to the cytoplasm. Ferroptosis inhibition by Fer‐1 might be a promising strategy to reduce BBB permeability after hypoxia exposure.